Frequency of FCGR3B alleles in Thai blood donors - Chollanot Kaset (2018)
Background: Human neutrophil antigens (HNAs) are involved in autoimmune and alloim-mune neutropenia and transfusion-related acute lung injury. The HNA-1 system is important in immunogenetics, and allele frequencies have been described in different populations. This study investigated the frequency of FCGR3B alleles encoding HNA-1a, HNA-1b, and HNA-1c among Thai blood donors and compared these frequencies with those previously reported for other populations. Methods: Eight hundred DNA samples obtained from unrelated healthy blood donors at the National Blood Centre, Thai Red Cross Society, Bangkok, and the Blood Bank, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand, were included. Samples were simultaneously typed for each FCGR3B allele using an in-house polymerase chain reaction with sequence-specific primer (PCR-SSP) technique. Results: The frequencies of FCGR3B*1, FCGR3B*2, and FCGR3B*3 alleles in central Thai blood donors were 0.548, 0.452, and 0.004, respectively; only FCGR3B*1 and FC-GR3B*2 alleles were found in northern Thai blood donors (0.68 and 0.32, respectively). Compared with other Asian populations, central Thais had higher frequencies of the FC-GR3B*2 allele (P<0.001), while the frequencies of the FCGR3B*1 and FCGR3B*2 alleles in northern Thais were similar to those previously reported in Taiwanese and Japanese populations. In contrast, the frequencies of the FCGR3B*1 and FCGR3B*2 alleles in the northern Thai population were statistically different from those observed in central Thai, Korean, German, and Turkish populations. Conclusions: FCGR3B allele frequencies were significantly different between central and northern Thai blood donors. Our in-house PCR-SSP method is a simple, cost-effective, and convenient method for FCGR3B allele detection. © The Korean Society for Laboratory Medicine.